Structural Equation Modeling for the Business Performance of Private Hospitals in Thailand: Management Perspective - Mallika Subongkod; Bharis Hongsakul (ABAC Journal, 2024)
This research aimed to study the causal factors affecting the business performance of private hospitals in Thailand from a management perspective. The sample consisted of 411 executives from private hospitals in Thailand, selected through purposive sampling. Data were collected via questionnaire, with SEM being used for analysis. The results indicated that the development of an enterprise resource system, including the competency and capability of entrepreneurs, positively influenced the focus on competitive differentiation. In turn, this focus had a positive effect on customer relationship management. Customer relationship management positively impacted brand loyalty, which subsequently enhanced business performance. In contrast, the competency and capability of entrepreneurs did not have an effect on business performance. The findings suggest that the growth and sustainability of business performance in private hospitals depends on various supportive factors. These range from policy formulation and the development of technological systems in services to strategies for building customer relationships, all contributing to competitive advantages, service loyalty, and success in achieving set goals.
Keywords: Customer Service Quality and Loyalty